Lifestyle and health vulnerabilities of people with disabilities in the COVID-19 pandemic - Oliveira, Paula Marciana Pinheiro de; Silva, Gisele Mendes da; Luzia, Francisco Jardsom Moura; Aquino, Sonha Maria Coelho de; Costa, Edmara Chaves; Carvalho, Carolina Maria de Lima; Grimaldi, Monaliza Ribeiro Mariano (Revista de Enfermagem da UFPI, 2024)
Objective: To analyze the vulnerabilities related to lifestyle and health of people with disabilities in the COVID-19 pandemic. Methods: This cross-sectional study analyzed the characteristics and health perceptions of 250 people with disabilities based on home visits using the reference network or snowball sampling strategy. A questionnaire was used to collect data on type of disability, cause, duration, physical activity, smoking and alcohol consumption, use of continuous medication, and pre-existing diseases. The chi-square test was used to analyze the data for compliance, frequency, percentages and p-values. Results: People with motor disabilities, acquired over the course of their lives and related to disease complications, predominated. With regard to health vulnerabilities, lack of physical exercise and continuous medication use were predominant. However, most respondents reported that they did not smoke or drink alcohol. Conclusion: The health and lifestyle vulnerabilities of people with disabilities identified in this study could help in the development of actions aimed at promoting the quality of life and health of this population, as well as in the identification of risk factors to be considered when designing health policies.